Food provision at the Olympic Games in the new millennium: a meta-narrative review - Pelly, F. E.; Tweedie, J.; O`Connor, H. (Sports Medicine - Open, 2023)
This meta-narrative review provides a comprehensive overview of food provision and at the Olympic and Paralympic Games (and similar scoped major competition events) over the past 21 years (since 2000) and discusses future challenges. Information sources included both grey literature (media, periodicals), official reports and evidence-based studies, reviews, book chapters and theses.